Forecasting Analysis of Production and Price of Red Chili (Capsicum annum L) in Southeast Sulawesi Province. - Khatimah, Husnul; Gusmiarty Abdullah, Weka; Abdi, Abdi (Journal of Food System & Agribusiness, 2023)
Red chili is a horticultural commodity that has high economic value and attractive market prospects for farmers but the production and price of chili peppers continue to fluctuate. The purpose of this research is to: Analyze Forecasting the production and price of red chili (Capsicum Annum L.) in Southeast Sulawesi in 2022-2026 using the Double Exponential Smoothing method. The method of determining the research area used is purposively where the production and price of red chili in Southeast Sulawesi Province fluctuates and the data used is secondary data obtained from the Central Bureau of Statistics of Southeast Sulawesi Province from 2012 to 2021. The data analysis technique used in this research is Double Exponential Smoothing. The highest predicted red chili production forecasting results are in 2022 amounting to 16,683 Quintals and the lowest is in 2026 amounting to 16,002 Quintals. The results of the analysis of forecasting the production and price of red chili in 2022-2026, namely the production of red chili in Southeast Sulawesi Province has decreased production every year while the price of red chili has increased in price every year.